América, Montaigne’s and Cervantes’s other - Marinas, Jose-Miguel (Tropelías: Review of Literary Theory and Comparative Literature, 2019)
The present text reflects on the way the West Indies and America are seen. Not so much the details that come with the new content, but rather the new way of perceiving and considering a world born of the radical event of discovery, conquest, colonization, and exploitation. Therefore examining the perspective, rather than what is seen, is the task at hand. This exercise will focus on two examples that are both similar and at the same time independently important: those of Michel de Montaigne and Miguel de Cervantes. The work will consist of three steps: (a) linking the American perspective with the modern south; (b) presenting some evidence and structure of American rhetoric in Montaigne; (c) and comparing those with examples from Cervantes.